Soliton Taxonomy for a Modification of the Lattice Boussinesq Equation - Hietarinta, J.; Zhang, D. (Symmetry, Integrability and Geometry: Methods and Applications, 2011)
Integrable multi-component lattice equations of the Boussinesq family have been known for some time. Recently some new equations of this type were found using the Consistency-Around-the-Cube approach. Here we investigate one of these models, B-2, and in particular the consequences of a nonzero deformation parameter b₀ > 0, which allows special kinds of solitons in the parameter range −b₀/3 < k < b₀.